돼지 체세포복제 35일령 태아에서 H19 메틸화 가변 영역의 DNA 메틸화 변화 - 고응규; 임기순; 황성수; 오건봉; 우제석; 조상래; 최선호; 이풍연; 연성흠; 조재현 (Journal of animal reproduction & biotechnology (Online), 2011)
This study was performed to identify the differentially methylated region (DMR) and to examine the mRNA expression of the imprinted H19 gene in day 35 of SCNT pig fetuses. The fetus and placenta at day 35 of gestation fetuses after natural mating (Control) or of cloned pig by somatic cell nuclear transfer (SCNT) were isolated from a uterus. To investigate the mRNA expression and methylation patterns of H19 gene, tissues from fetal liver and placenta including endometrial and extraembryonic tissues were collected. The mRNA expression was evaluated by real-time PCR and methylation pattern was analyzed by bisulfite sequencing method. Bisulfite analyses demonstrated that the differentially methylated region (DMR) was located between —1694 bp to —1338 bp upstream from translation start site of the H19 gene. H19 DMR (—1694 bp to —1338 bp) exhibits a normal monoallelic methylation pattern,and heavily methylated in sperm, but not in oocyte. In contrast to these finding, the analysis of the endometrium and/or extraembryonic tissues from SCNT embryos revealed a complex methylation pattern. The DNA methylation status of DMR RegionⅠn porcine H19 gene upstream was hypomethylated in SCNT tissues but hypermethylated in control tissues. Furthermore, the mRNA expression of H19 gene in liver, endometrium, and extraembryonic tissues was significantly higher in SCNT than those of control (p<0.05). These results suggest that the aberrant mRNA expression and the abnormal methylation pattern of imprinted H19 gene might be closely related to the inadequate KCI Citation Count: 0